Instrumen Kemampuan Pemecahan Masalah Bangun Ruang Sisi Datar pada Konteks Rumah Adat Baduy - Khaerunnisa, Etika; Muhyidin, Asep; Leksono, Suroso Mukti (Universitas Sultan Ageng Tirtayasa, 2025)
This study aims to develop a mathematical problem-solving ability instrument within the context of traditional Baduy houses for the topic of three-dimensional geometric shapes and to examine its potential effects. The research adopts a development research design. The subject of this study is 8th-grade junior high school students, who participated in solving the mathematical problem-solving instrument contextualized in traditional Baduy architecture. Data analysis techniques involved both qualitative and quantitative approaches. Qualitative analysis was used to describe and examine expert validation data and instrument practicality based on observations during small group implementation. Quantitative analysis was employed to assess the validity of the test items, including item validity and reliability. Student responses were evaluated based on a scoring rubric for mathematical problem-solving ability. The results of the analysis were used to revise the test items developed by the researchers. The findings indicate that (1) the study successfully developed six valid essay-type items measuring mathematical problem-solving ability in the context of traditional Baduy houses for the topic of three-dimensional geometric shapes, and (2) the developed instrument demonstrated good potential effects on students’ mathematical problem-solving performance, as reflected by the overall good category achieved in the test results.